Relationship between energy cost, swimming velocity, speed fluctuation in competitive swimming strokes - Barbosa, Tiago M. (2011)
The purpose of this study was to analyse the relationships between the total energy expenditure ( tot), the energy cost (EC), the intra-cycle variation of the horizontal velocity of displacement of centre of mass (dv) and the mean swimming velocity (v) in the four competitive swimming strokes.